REVITALIZATION OF QURANIC READING QUALITY IN COASTAL COMMUNITIES POST-TSUNAMI: A STUDY IN GLEE BRUEK LHOONG VILLAGE, ACEH BESAR - Suarni, Suarni; Syukrinur, Syukrinur (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2024)
The Qur'an is a holy book that has specific rules for its recitation so that the meanings contained within it can be correctly understood. Errors in pronunciation can affect the meaning and the purpose of worship. After the tsunami, the ability of the people of Glee Bruek to recite the Qur'an has shifted, particularly in the application of Tajweed rules. This study aims to identify the ability and efforts of the Glee Bruek community in improving the quality of Qur'an recitation after the tsunami, in accordance with Tajweed principles. The research method used is qualitative-descriptive analysis. The results of the study show that the limited ability to recite the Qur'an in the Glee Bruek community is due to the loss of many religious leaders in the tsunami. However, the community has started to rebuild places for Qur'anic study in their homes. The conclusion of this study is that the effort to rebuild places of Qur'anic study plays an important role in improving the quality of Qur'anic recitation in Glee Bruek.